2019
DOI: 10.1016/j.amsu.2019.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Case series of in situ pelvic floor reconstruction combining levator ani suture and negative pressure wound therapy for abdominoperineal resection

Abstract: Background Abdominoperineal resection (APR) is a standard surgical technique for low rectum cancer with a low recurrence rate. There are some problems associated with APR such as perineal hernia and perineal surgical site infection. Recently, the prophylactic efficacy of negative pressure wound therapy (NPWT) for surgical site infection has been reported. Herein, we analyzed the efficacy of in situ pelvic floor reconstruction combining levator ani suture and NPWT after APR for perineal hernia and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…14 No factors have been strongly established to increase the risk of PH, although multiple factors have been identified as potential risk factors; these include obesity, diabetes, chemoradiotherapy, and extensive pelvic floor resections (eg, ELAPR). 4,5,7,10 In our series, most patients had received neoadjuvant CRT, suggesting that it may be a risk factor contributing to the development of PH; however, our study is underpowered with no controls. This finding was similar to McKenna et al 11 , Martijnse et al 10 , and Abbas & Garner 5 in that the majority of their patients had received neoadjuvant CRT; this may indicate an effect on wound healing, or it may be that most patients undergoing APR for rectal cancer receive neoadjuvant CRT.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…14 No factors have been strongly established to increase the risk of PH, although multiple factors have been identified as potential risk factors; these include obesity, diabetes, chemoradiotherapy, and extensive pelvic floor resections (eg, ELAPR). 4,5,7,10 In our series, most patients had received neoadjuvant CRT, suggesting that it may be a risk factor contributing to the development of PH; however, our study is underpowered with no controls. This finding was similar to McKenna et al 11 , Martijnse et al 10 , and Abbas & Garner 5 in that the majority of their patients had received neoadjuvant CRT; this may indicate an effect on wound healing, or it may be that most patients undergoing APR for rectal cancer receive neoadjuvant CRT.…”
Section: Discussionmentioning
confidence: 84%
“…P erineal hernia (PH), although rare, is a well-known complication following abdominoperineal resection (APR) for rectal cancer and has been defined as a defect in the pelvic floor through which abdominal and/ or pelvic viscera protrude. [1][2][3][4][5][6][7][8] The reported incidence varies from less than 1% to 13%; [3][4][5][6][8][9][10][11] in our previous study, we found an incidence of 1%. 12 Due to its rarity, the literature on surgical PH repair is comprised of case reports and small case series, and not one surgical approach has been established as superior.…”
Section: Principales Medidas De Resultadomentioning
confidence: 92%
See 2 more Smart Citations
“…Various pelvic reinforcements as alternatives to PPC have been performed after APE: suture of levator ani muscle, bladder peritoneal flaps, hysteropexy, omentoplasty and synthetic mesh. Levator ani muscle suturing [25] could not be applied to rectal cancer surgery because of wide excision of the muscle. A randomized trial revealed that omentoplasty did not reduce the incidence of PPH [26].…”
Section: Discussionmentioning
confidence: 99%